Factors Relating to the Interest of Use MKJP (IUD and Implant) in the Village of Perigi Mekar, Ciseeng, Bogor - Marlynda Happy Nurmalita Sari; Aprida Sopiani; Ade Irawati (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2020)
The use of MKJP in Indonesia has decreased every year from 13.7% in 1991 to 10.6% in 2012 (Ministry of Health, 2013). In 2013, based on a mini survey of the Population and Family Planning Agency (BKKBN), the coverage of MKJP in Indonesia was only 12.4% with a percentage based on the type of method, namely KB implants (5.2%), IUD (Contraceptive Devices in the Womb) / Intrauterine Device (IUD) (4.7%), and Women's Operations Method (MOW) (2.2%), whereas the expected MKJP target is 26.7%. This research is descriptive analytic, conducted to determine factors related to the interest in using MKJP (IUD Implants) in Perigi Mekar Village in 2016. The number of samples in this study were 104 people. Data were collected using a questionnaire. Of the 9 variables studied, 2 variables showed a significant relationship with the interest in using the MKJP is income with a p value of 0.018, and discussions with a partner with a p value of 0.024. From the above statement it can be concluded that the amount of income and the frequency of discussions with partners influences the interest in using the MKJP. It is expected that community leaders can work together with local health workers so that they can provide counseling to the community regarding long-term contraceptive methods. Keyword : Contraception, MKJP, IUD, Implant